Perceptions of immunity and vaccination certificates among the general population: a nested study within a serosurvey of anti-SARS-CoV-2 antibodies (SEROCoV-POP) (Swiss Medical Weekly, 2020)
At a time when COVID-19 immunity certificates are debated and vaccination certificates might potentially be made available if an effective vaccine is established, we conducted a study to elucidate public opinion on this issue. Our objective was to determine social and individual perceptions of COVID-19 immunity certificates through a population-based study. A nested survey within the SEROCoV-POP study, a population-based serosurvey of anti-SARS-CoV-2 IgG antibodies in Geneva, Switzerland, was conducted with a self-administered questionnaire. The questionnaire was proposed to 1520 SEROCoV-POP participants. Measures included percentage of participants agreeing or disagreeing with statements on immunity and vaccination certificates. Stratification by age, gender, education and work status was used to examine socio-demographic variations. Of the 1520 SEROCoV-POP participants, 1425 completed the questionnaire (response rate 93%; mean age ± standard deviation 52 ± 15.1 years; 51.9% women). About 80% of participants agreed that knowing one’s serology status would lead to a change in one’s behaviour. In the event that the presence of antibodies correlated with immunity, 60% of participants reported that certificates should be offered to the general population. The results showed variations in perceptions of certificates depending on the context (73% agreed on certificates’ utility for travel, 72% for entering a country, and 32% for the right to work). Provided an effective vaccine was available, 55% of participants agreed that vaccination should be mandatory and 49% agreed that a vaccination certificate should be mandatory. About 68% reported a potential risk of discrimination and 28% a risk of deliberate infection. Differences were seen with age, gender and education level. This study shows that the general adult population in Geneva, Switzerland can envisage scenarios where COVID-19 immunity, and eventually vaccination, certificates would be useful. Seroprevalence estimates of anti-SARS-CoV-2 antibodies remain low to date, and the interpretability of serological testing and immunity remains undefined. However, the information from this study is important, especially the differences based on context and the socio-demographic variations, and should be taken into account if COVID-19-related certificates are to be implemented.